Role of The Local Government Operating Act in The Execution of Federalism and Local Administration in Nepal - Adhikari, Hari Prasad (Universitas Madura, 2024)
This study was to examine the contribution of local government operating Act. (LGOA), 2074for the implementation of federalism and local governance in Nepal. Descriptive and analytical research design was used in this study. The data collected through questionnaire from 150 respondents was used for analysis. An execution of the contribution of local government Operating Act in Nepal was found satisfactory, but its contribution was found poor because of poor implementation. The findings from this study can provide information about the contribution of local government operating Act for the implementation of federalism and local governance in Nepal. It could be helpful to provide some special guidelines to the policy makers for improving local governance. In addition appropriate policy must be adopted and sound communication and information system should be developed.